2018
DOI: 10.1038/s41598-018-36441-w
|View full text |Cite
|
Sign up to set email alerts
|

GeVn complexes for silicon-based room-temperature single-atom nanoelectronics

Abstract: We propose germanium-vacancy complexes (GeVn) as a viable ingredient to exploit single-atom quantum effects in silicon devices at room temperature. Our predictions, motivated by the high controllability of the location of the defect via accurate single-atom implantation techniques, are based on ab-initio Density Functional Theory calculations within a parameterfree screened-dependent hybrid functional scheme, suitable to provide reliable bandstructure energies and defect-state wavefunctions. The resulting defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 58 publications
(82 reference statements)
1
16
0
Order By: Relevance
“…Based on ab initio calculations, [ 3 ] some of us have recently demonstrated that Ge V complexes in silicon are stable defects, characterized by excited states deep in the bandgap, at about ≃−0.5 eV and ≃−0.35 eV from the conduction band, consistent with experiment. [ 23 ] Such impurity states have large on‐site electron–electron repulsion (≃150 meV) due to their highly localized wavefunctions (the decay length of the lowest charged state is ≃0.45 nm).…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…Based on ab initio calculations, [ 3 ] some of us have recently demonstrated that Ge V complexes in silicon are stable defects, characterized by excited states deep in the bandgap, at about ≃−0.5 eV and ≃−0.35 eV from the conduction band, consistent with experiment. [ 23 ] Such impurity states have large on‐site electron–electron repulsion (≃150 meV) due to their highly localized wavefunctions (the decay length of the lowest charged state is ≃0.45 nm).…”
Section: Introductionsupporting
confidence: 68%
“…We evaluate the hopping and inter‐site repulsion parameters using the wavefunction of the electronic state occupied by an additional electron on the defect, namely the charged excitation sitting −0.5 eV below the conduction‐band bottom. [ 3 ] The use of a wavefunction obtained from ab initio calculation allows a more accurate description of deep energy levels of Ge V with respect to the usually adopted Kohn–Luttinger wavefunction which is suitable for shallow levels of conventional dopants but not appropriate for Ge V . Figure 1a shows a section of such ab initio‐computed wave function across a high‐symmetry crystal plane through two vacancy centers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other solution is by improving the quantum efficiency by sophisticated Si doping techniques such as deterministic doping 31 to control the donor bands’ energy spread. In addition, by using a variety of donors and acceptors, it is possible to operate in a different bandwidth such as in the near-infrared range by using a deep level dopant (e.g., ~0.51 eV Ge-vacancy center as a donor 32 ). An additional advantage of using Si nanotechnology is that arrayed Si-QD detectors are compatible with mature Si integrated circuit technologies for multiple signal processing and amplification techniques, which can then be applied to THz cameras in the future.…”
Section: Resultsmentioning
confidence: 99%